APPRAISAL OF PRESENT SITUATION OF HYPERTENSION IN PORT CITY CHATTOGRAM, BANGLADESH - Islam, Md. Shahidul; Jannat, Tasnuba (Universal Journal of Pharmaceutical Research, 2022)
Background: Hypertension is a very much common disease. While data collection on hypertension in resource poor environments has been improving through the use of standardized surveys, little is known about how well treatments are being applied. Knowledge of gaps in diagnosis, treatment pattern and changing lifestyle is necessary if appropriate illness management are to developed. Methods: Using a community based sample has been taken from Chittagong Medical College Hospital, Chittagong and from the Chittagong city, studied through some questions asked to the suspicious patients. Results: Randomized sampling methods were used to identify adults from 18 to above from different wards and areas of CMCH and Chittagong city. Using World Health Organizations guidelines, data were collected on subject’s demographics, medical history, blood pressure and health behaviors. The study was conducted on 500 hypertensive patients at the Chittagong Medical College Hospital and Chittagong city between 23October 2021 to 8 December 2021, total 7 weeks. This survey was done by a structured questionnaire written in Bangla and English. Conclusion: It might be concluded from this research study that half of respondents were female in addition to half of respondents were male. It can be assumed that outcomes of this research study will play as the baseline for the future studies in same context. Peer Review History: Received: 2 December 2021; Revised: 5 January 2022; Accepted: 9 February, Available online: 15 March 2022 Academic Editor: Dr. Sally A. El-Zahaby , Pharos University in Alexandria, Egypt, sally.elzahaby@yahoo.com Reviewers: Prof. Dr. Hassan A.H. Al-Shamahy, Sana’a University, Yemen, shmahe@yemen.net.ye Dr. Rima Benatoui, Laboratory of Applied Neuroendocrinology, Department of Biology, Faculty of Science, Badji Mokhtar University Annaba, BP12 E L Hadjar–Algeria, benattouiryma@gmail.com